A Study on the Composition and Communication of Chinese Character Images under the Context of Digital New Media. Issue 5 (October 2020) - Liu, Lin; Wang, Yudi
Abstract: Under the context of digital new media, the paper deals with the composition and dissemination of Chinese character images from three perspectives: the structure and communication of the character images, the presentation of character images and the modes of communication. Due to the computer technologies, Chinese characters could be presented on the screen with both pictures and sounds and become more intuitive and realistic. What's more, the light effects and dynamic technique feature prominent in forming visual images of Chinese characters. In a word, the computer technologies help to realize the multi-dimensional and dynamic presentation of Chinese characters.